2019
DOI: 10.1055/s-0038-1677031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestation and Mutation Spectrum of 53 Unrelated Pedigrees with Protein S Deficiency in China

Abstract: Protein S (PS) deficiency is associated with a 10-fold increased risk of venous thromboembolism (VTE), but its diagnosis is quite difficult and complicated. In this study, we identified 53 unrelated pedigrees with PS deficiency in China. Data of their clinical characteristics and laboratory examinations were collected. Genetic analysis of PROS1 including direct sequencing, copy number variant detection and messenger ribonucleic acid analysis was performed in probands and related family members. Of these 53 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…Homozygous or compound heterozygous PS deficiency is extremely rare, usually presenting with massive VTE or purpura fulminans neonatally 1 25. In the recent 20 years, several reports of compound heterozygosity with later onset of VTE were also available in the literature 22 26–29. The probands in these studies remained free of thrombosis until they became teenagers and suffered from recurrent thrombosis after that, which was the same as the propositus reported in our own study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Homozygous or compound heterozygous PS deficiency is extremely rare, usually presenting with massive VTE or purpura fulminans neonatally 1 25. In the recent 20 years, several reports of compound heterozygosity with later onset of VTE were also available in the literature 22 26–29. The probands in these studies remained free of thrombosis until they became teenagers and suffered from recurrent thrombosis after that, which was the same as the propositus reported in our own study.…”
Section: Discussionsupporting
confidence: 76%
“…In a young Chinese man who suffered from recurrent venous thrombosis with very low level of PS activity, we have identified compound heterozygous mutations, one novel small indel mutation and one missense mutation in PROS1 gene, the latter of which was reported before by other study groups,21 22 but the pathological mechanism remained unknown. In the current study, the relationship between the genotype and phenotype detection was analysed by thrombin generation test (TGT), and the pathological mechanisms of these two mutations causing PS deficiency were further investigated by recombinant PS expression experiments in vitro.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…But the incidence bias may be existed because the majority of patients were referred to our center by local clinicians for screening the thrombotic risk factors after the diagnosis of first or recurrent VTE. 27 Ultimately, we chose 17 AT-deficient, 39 PC-deficient, 38 PS-deficient, and 6 combined anticoagulant-deficient patients from our center to constitute the thrombophilia group. It is worth noting that these values only represented the composition of the 3 defects in this group rather than the incidences in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Some intronic splice variants (Choi et al , 2011; Menezes et al , 2017; Wang et al , 2019) and structural variants (Hurtado et al , 2009; Lind-Halldén et al , 2012; Seo et al , 2014) have also been reported. Note that, compared to exonic variations, very few variations have been described in the promoter region of the PROS1 gene (Espinosa-Parrilla et al , 2000; Hurtado et al , 2008; Li et al , 2019; Sanda et al , 2007; Tang et al , 2013) and even fewer have been functionally characterized. To our knowledge, the c.-168C>T is the sole PROS1 promoter variation that has been experimentally demonstrated to cause inherited PSD by affecting the core binding site of Sp1 transcription factor (Sanda et al , 2007).…”
Section: Introductionmentioning
confidence: 99%